2008
DOI: 10.1038/cr.2008.44
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis MutS homolog AtMSH5 is required for normal meiosis

Abstract: npg MSH5, a member of the MutS homolog DNA mismatch repair protein family, has been shown to be required for proper homologous chromosome recombination in diverse organisms such as mouse, budding yeast and Caenorhabditis elegans. In this paper, we show that a mutant Arabidopsis plant carrying the putative disrupted AtMSH5 gene exhibits defects during meiotic division, producing a proportion of nonviable pollen grains and abnormal embryo sacs, and thereby leading to a decrease in fertility. AtMSH5 expression is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 38 publications
3
37
0
Order By: Relevance
“…Copenhaver et al (2002) were able to fit Arabidopsis data to a counting model for interference (Foss et al 1993) if they assumed two types of crossovers: some that participate in interference and some that do not. Consistent with this prediction, experimental studies demonstrated that the residual crossovers in Arabidopsis and budding yeast msh4 and msh5 mutants do not display interference (Novak et al 2001;Argueso et al 2004;Higgins et al 2004;Lu et al 2008), as predicted by Zalevsky et al (1999). Conversely, Mus81-Mms4-independent crossovers in S. cerevisiae and Arabidopsis do exhibit interference (de los Santos et al 2003;Berchowitz et al 2007).…”
Section: Rise Of the Two-pathway Paradigmsupporting
confidence: 60%
“…Copenhaver et al (2002) were able to fit Arabidopsis data to a counting model for interference (Foss et al 1993) if they assumed two types of crossovers: some that participate in interference and some that do not. Consistent with this prediction, experimental studies demonstrated that the residual crossovers in Arabidopsis and budding yeast msh4 and msh5 mutants do not display interference (Novak et al 2001;Argueso et al 2004;Higgins et al 2004;Lu et al 2008), as predicted by Zalevsky et al (1999). Conversely, Mus81-Mms4-independent crossovers in S. cerevisiae and Arabidopsis do exhibit interference (de los Santos et al 2003;Berchowitz et al 2007).…”
Section: Rise Of the Two-pathway Paradigmsupporting
confidence: 60%
“…We next analyzed a fancm-1 msh4-1 double mutant. Although SC formation is normal, albeit delayed, in a msh4-1 mutant, loss of the gene results in a strong reduction in fertility due to a dramatic reduction in CO formation (Higgins et al, 2004(Higgins et al, , 2008bLu et al, 2008). Surprisingly, fancm-1 msh4-1 homozygous plants produced considerably more seeds per silique than msh4-1 (19.88 versus 4.0, respectively), although this was not as high as fancm-1 (41.36).…”
Section: Analysis Of At-fancm Function Within Meiotic Pathwaysmentioning
confidence: 78%
“…However, the functions of these proteins for SC assembly are divergent in other organisms. In Arabidopsis, no apparent defects in chromosome synapsis are observed in msh5 and zip4 mutants (Chelysheva et al, 2007;Higgins et al, 2008;Lu et al, 2008). In the msh4 mutant, chromosome synapsis might be incomplete but the defects are not severe (Higgins et al, 2004).…”
Section: Introductionmentioning
confidence: 97%